Evaluasi Pembelajaran PAI dalam Membentuk Karakter Religius Peserta Didik di MI Miftahul Ulum Wirowongso Ajung - Muhammad Tis Asuh Sobirin; Moh. Sahlan (4, 2026)
This study aims to evaluate the Islamic Religious Education (PAI) learning program in shaping the religious character of students at MI Miftahul Ulum Wirowongso Ajung. The study used a qualitative approach with an evaluative research type through the Context, Input, Process, Product (CIPP) model. Research informants consisted of the madrasah principal, Islamic Religious Education teachers, homeroom teachers, and students who were selected purposively. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and drawing conclusions. The results showed that the PAI learning program has run well in the aspects of context, input, process, and results. The program is supported by the madrasah's vision that is oriented towards the formation of religious character, teacher competence and adequate learning tools, as well as the implementation of learning that integrates role models, worship habits, and formative and summative assessments. The impact of the program is seen in the increase in worship habits, discipline, honesty, responsibility, and politeness of students. This study recommends strengthening innovation in learning strategies, developing digital-based learning media, and optimizing collaboration between madrasas, parents, and the community so that the formation of students' religious character takes place sustainably. Abstrak. Penelitian ini bertujuan untuk mengevaluasi program pembelajaran Pendidikan Agama Islam (PAI) dalam membentuk karakter religius peserta didik di MI Miftahul Ulum Wirowongso Ajung. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian evaluatif melalui model Context, Input, Process, Product (CIPP). Informan penelitian terdiri atas kepala madrasah, guru Pendidikan Agama Islam, wali kelas, dan peserta didik yang dipilih secara purposive. Data dikumpulkan melalui observasi, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa program pembelajaran PAI telah berjalan dengan baik pada aspek konteks, masukan, proses, dan hasil. Program didukung oleh visi madrasah yang berorientasi pada pembentukan karakter religius, kompetensi guru dan perangkat pembelajaran yang memadai, serta pelaksanaan pembelajaran yang mengintegrasikan keteladanan, pembiasaan ibadah, dan asesmen formatif maupun sumatif. Dampak program terlihat dari meningkatnya kebiasaan beribadah, kedisiplinan, kejujuran, tanggung jawab, dan sikap santun peserta didik. Penelitian ini merekomendasikan penguatan inovasi strategi pembelajaran, pengembangan media pembelajaran berbasis digital, serta optimalisasi kolaborasi antara madrasah, orang tua, dan masyarakat agar pembentukan karakter religius peserta didik berlangsung secara berkelanjutan.